2023
DOI: 10.1080/21645515.2023.2269794
|View full text |Cite
|
Sign up to set email alerts
|

Research trends on immunotherapy for pancreatic cancer: A bibliometric analysis

Jubao Niu,
Wenkai Jiang,
Dongao Fan
et al.

Abstract: This study aims to summarize and visually analyze the current research status in pancreatic cancer immunotherapy during the past two decades by bibliometrics and explore the current research hotspots and future development directions. The literature related to pancreatic cancer immunotherapy from 2002 to 2021 was downloaded from the core database of the Web of Science. VOSviewer and CiteSpace software were used to visualize the included literature. A total of 2528 articles were included. In the past two decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The top 10 journals published 146 papers, accounting for 23.03% of all publications ( Table 4 ). Cancers published the most papers with 31 papers, followed by International Journal of Molecular Sciences ( 24 ), Frontiers in Oncology ( 18 ), Cancer Letters ( 14 ), Scientific Reports ( 12 ), Analytical Chemistry ( 11 ). Although ACS Nano has only published 9 articles, it has the highest total citations (1363) and average citations (151.44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top 10 journals published 146 papers, accounting for 23.03% of all publications ( Table 4 ). Cancers published the most papers with 31 papers, followed by International Journal of Molecular Sciences ( 24 ), Frontiers in Oncology ( 18 ), Cancer Letters ( 14 ), Scientific Reports ( 12 ), Analytical Chemistry ( 11 ). Although ACS Nano has only published 9 articles, it has the highest total citations (1363) and average citations (151.44).…”
Section: Resultsmentioning
confidence: 99%
“…The purpose is to deeply understand the research status of specific fields, research hotspots and predict future research trends ( 15 17 ). In recent years, bibliometric has also been applied to immunotherapy, autophagy therapy, neoadjuvant therapy, and tumor microenvironment of PC ( 18 21 ), but no bibliometric research or visual analysis of exosomes in PC has been reported. By searching the Web of Science Core Collection (WOSCC), a comprehensive bibliometric analysis was conducted on the literature related to exosome in PC from 2013 to 2023.…”
Section: Introductionmentioning
confidence: 99%